Three tanks water level monitoring system (hardware development)/ Zuhairi Ghazali - Ghazali, Zuhairi (1999)
Measuring or monitoring of the level of material contained in storage and processing vessels, such as tanks is one of the most common procedures of industrial instrumentation. Recently, die technologies developed specially in computers enable us to provide an incentive for the application of computer-aided methods in monitoring the level. The main objective of this project is to develop the hardware components that can be used in monitoring the water level in three tanks water system by using computer without affecting the plant control system. This pilot plant gives a closer looks and understanding about the real monitoring process.